Selective neuronal degeneration in the retrosplenial cortex impairs the recall of contextual fear memory - Sigwald D'alesio, Eric Luca (2016)
The retrosplenial cortex (RSC) is one of the largest cortical areas in rodents, and is subdivided in two main regions, A29 and A30, according to their cytoarchitectural organization and connectivities. However, very little is known about the functional activity of each RSC subdivision during the execution of complex cognitive tasks. Here, we used a well-established fear learning protocol that induced long-lasting contextual fear memory and showed that during evocation of the fear memory, the expression of early growth response gene 1 was up-regulated in A30, and in other brain areas implicated in fear and spatial memory, however, was down-regulated in A29, including layers IV and V. To search for the participation of A29 on fear memory, we triggered selective degeneration of neurons within cortical layers IV and V of A29 by using a non-invasive protocol that takes advantage of the vulnerability that these neurons have MK801-toxicity and the modulation of this neurodegeneration by testosterone. Application of 5 mg/kg MK801 in intact males induced negligible neuronal degeneration of A29 neurons and had no impact on fear memory retrieval. However, in orchiectomized rats, 5 mg/kg MK801 induced overt degeneration of layers IV–V neurons of A29, significantly impairing fear memory recall. Degeneration of A29 neurons did not affect exploratory or anxiety-related behavior nor altered unconditioned freezing. Importantly, protecting A29 neurons from MK801-toxicity by testosterone preserved fear memory recall in orchiectomized rats. Thus, neurons within cortical layers IV–V of A29 are critically required for efficient retrieval of contextual fear memory.